PELAKSANAAN DAN HAMBATAN PERKAWINAN TUNGKU CU PADA MASYARAKAT ADAT MANGGARAI DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Afriana Sulastri Murni; Jeane Neltje Saly (Jurnal Hukum Adigama, 2022)
This journal aims to inform the Indonesian people in general and to the Manggarai community in particular which in this study concerns implementation and is also related to obstacles for couples who marry with the Tungku Cu relationship, which in this case is a custom or custom of the community in Manggarai. The process of collecting data and research on this journal was carried out in the period from August 2022 to December 2022. The research method used by the author in this study is the Normative research method and the data collection technique carried out is with a literature study which is also corroborated by opinions from those related to being based on interviews with sources. Tungku Cu marriage has pros and cons in the Manggarai community in particular which in this study will be represented by the resource persons whom the author interviewed in this study related to the implementation and obstacles of Tungku Cu marriage in Manggarai which until now there are still several couples married to the Tungku Cu relationship in Manggarai, Flores, East Nusa Tenggara.